Structural and cellular characterization of solvent-casted polyurethane membranes - (:unkn) unknown (My University, 1990)
Fibroblastic cell attachment and growth characteristics of different polyurethane (PU) films were tested. These films were prepared by a classical solvent-casting procedure. By changing the composition and the type of casting solution (i. e. tetrahydrofurane, dioxane, dimethyl formamide-tetrahydrofurane, tetrahydrofurane-dioxane, etc.) PU films with different physical and chemical bulk and surface structures were obtained. Structural properties of these films were investigated by scanning electron microscopy, equilibrium swelling experiments and contact-angle studies. In stationary cell culture tests, a model cell-line, i.e. baby hamster kidney (BHK) were used. Thus the effects of structural properties on the cell behaviour were investigated. The results demonstrate that it is possible to achieve different cell responses by changing the preparation conditions of the films. While the cell attachment is excellent on porous PU surfaces, the others showed similar adhesion. Better proliferation of BHK cells was obtained with PU films prepared from dioxane solution. © 1990.